Mammalian Target of Rapamycin Signaling Pathway Regulates Mitochondrial Quality Control of Brown Adipocytes in Mice - Huwatibieke, Bahetiyaer; Yin, Wenzhen; Liu, Lingchao; Jin, Yuxin; Xiang, Xinxin; Han, Jingyan; Zhang, Weizhen; Li, Yin (Frontiers in Physiology, 2021)
The mammalian target of rapamycin (mTOR) is an important protein kinase that senses changes in extracellular and intracellular energy levels and plays a key role in regulating energy metabolism. Brown adipose tissue, which can be converted to white adipose tissue, contains a large number of mitochondria and regulates energy expenditure through thermogenesis. Because obesity is a process of fat accumulation due to chronic excessive energy intake, we attempted to determine whether the mTOR signaling pathway can affect the mitochondrial quality control of brown adipocytes through sensing energy status, thereby regulating brown/white adipocyte transformation. In the present study, through activation or inhibition of mTOR signaling, we detected mitochondrial biogenesis, dynamics, and autophagy-related markers in brown adipocytes. We found that activation of mTOR signaling down-regulated the expression of mitochondrial biogenesis, dynamics, and autophagy-relevant markers; inhibited the mitochondrial quality control of brown adipocytes, indicating a phenotypic transformation of brown to white adipocytes. In contrast, inhibition of mTOR signaling up-regulated the expression of mitochondrial biogenesis, dynamics, and mitophagy-relevant markers; strengthened mitochondrial quality control, suggesting an inhibition of the phenotypic transformation of brown to white adipocytes. In conclusion, the mTOR signaling pathway plays an important role in modulating the transformation of adipocytes by regulating mitochondrial quality control.